Enhancing mathematics learning motivation in elementary school students through the make a match learning model - Rahma Tsani Azalia; Malzia Nazma Mauranissa; Rifa Nurul Aqilah; Rinaldi Yusup; Nor Syazwani Mohd Rasid (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to enhance the mathematics learning motivation of elementary school students through the implementation of the Make a Match learning model. The research background is based on the low motivation of students in participating in mathematics lessons, which impacts the lack of engagement and suboptimal learning outcomes. The method used is Classroom Action Research (CAR) with two cycles conducted in grade IV of SDN Bojongkawung, Sukabumi Regency, in the 2024/2025 academic year. The research subjects consisted of 18 students, and data were collected through observation, interviews, and attitude assessment instruments that included indicators of cooperation, responsibility, critical reasoning, and creativity. The research results indicate a significant increase in students' learning motivation, marked by an increase in the average attitude score from 40% in the pre-test to 55% in cycle I, and 74.25% in cycle II. The application of the Make a Match model creates a fun, interactive, and collaborative learning atmosphere, thereby encouraging students to be more active and enthusiastic in mathematics learning. Thus, the Make a Match model proves to be effective as a learning strategy that can enhance the learning motivation of elementary school students. This study contributes to the development of learning strategies that can enhance students' mathematics learning motivation through the implementation of an interactive and collaborative learning model.